Augusto Barrera y los medios impresos. - Andrade Rocha, Diego Fernando (2016)
Augusto Barrera and press media is a descriptive investigation work where is analized politic speechmaking of El Comercio and El Telegrafo in the elections for Municipality of Quito in 2014 february. The academic article analizes cualitative and cuantitative levels of speechmaking of both media press and their interference in elections where Augusto Barrera searched for relection. At long election campaign El Comercio and El Telegrafo, private and public press media - respectively- took politic position and with different periodistic style emphasize, qualify or denature news for generating public opinion, the one in favour and the other against Augusto Barrera candidate. Trough analysis of specheemaking in the media press mencioned is determined effectiveness of treatment of information, retoric uses and ideologic charge that both journals used for creating aceptation or rejection on Barrera´s candidature for Municipality.